Environmental diagnosis in areas with different use and occupation using the perception of diverse biological activity - Ribeiro, Admilson Írio [UNESP]; Peche Filho, A.; Medeiros, Gerson Araujo de [UNESP]; Longo, R. M.; Storino, M.; Fengler, F. H.; Keller, E. M. L.; Rapp, J. Z.; Freitas, E. P. (WITPRESS LTD., 2012)
In Brazil, the degradation of soil and landscape by urban and agricultural frontiers expansion leads to the need for comprehensive studies and consider the diverse biological activities generated from different interventions in the landscape, becoming an instrument for assessing the impacts and the decision for its environmental management. The objective of this study was to evaluate the influence of different forms of occupation of the landscape, considering ecological elements and their interactions. The work was carried out on the Instituto Agronômico in the county of Jundiai, in the state of Sao Paulo, Brazil. The area under study has been subjected to different use and occupancy for a period of about 40 years. During this period the landscape has been transformed, with the current scenario can be classified as a degraded area mining; grassy area; Araucaria forest and pasture. These areas were evaluated by means of a transect, from which ten sampling sites were selected for the description of diverse biological activities, which included: evaluation and description of ground cover, identifying the presence of fungus and insect species. Furthermore, we evaluated in these points the pH, fertility and porosity of the topsoil (0-0.10 m). The results showed a variation of the elements analyzed and a relationship between the use and occupation of land in the different scenarios of the current landscape. The biological activity was more diverse in the Araucaria forest, reflected by the abundance of litter, higher content of organic matter and soil nutrients, demonstrating the effectiveness of the technique for assessing the level of degradation of the landscape used, which is expeditious and inexpensive.
Keywords: Environmental impact; Land degradation; Soil restoration; agriculture; environmental impact assessment; environmental management; fertility; fungus; ground cover; insect; land degradation; landscape; litter; organic matter; perception; pH; porosity; soil degradation; soil nutrient; topsoil; urban area; Araucaria; Brazil; Jundiai; Parana [Brazil]; Sao Paulo [Brazil]; Fungi; Hexapoda